Age is more predictive of safe movement patterns than are physical activity or sports specialization: A prospective motion analysis study of young athletes - Heath, M. R.; Janosky, J. J.; Pegno, A.; Schachne, J. M.; Fabricant, P. D. (The American Journal of Sports Medicine, 2021)
Background: Movement quality and neuromuscular balance are noted predictors of acute injury. Early sports specialization and extremely high activity levels have been linked to elevated risk of injury.